La violència física i econòmica contra les dones a la Mallorca del segle XVII: una aproximació. - NICOLAU, VICTÒRIA BAUÇÀ (Scripta, 2020)
In this first approach to Mallorca in the seventeenth century, we can see how women suffered different types of violence. On the one hand, the physical violence was exercised both by strangers and by husbands within the conjugal environment. The most common solution to this violence was the escape of the woman who was being abused. In many cases, the dispute ended in divorce. On the other hand, we documented the existence of violence that can be called economic. This type of violence is based on the exclusion of women from their own possessions, which led to lengthy litigation for dowry restitution or to claim an inheritance. Generally, this violence occurred when women were left alone and in a situation of economic and social vulnerability. The economic violence was usually exercised by men close to the victims in different ways. However, we can highlight the vindictive and active disposition of Mallorcan women in the face of these types of violences.